1999
DOI: 10.1094/phyto.1999.89.10.967
|View full text |Cite
|
Sign up to set email alerts
|

Two Sibling Species of the Botrytis cinerea Complex, transposa and vacuma, Are Found in Sympatry on Numerous Host Plants

Abstract: Strains of Botrytis cinerea (the anamorph of Botryotinia fuckeliana) were collected from 21 different plant species around vineyards in the Champagne region (France). Strains were analyzed using three new polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) markers that were found by SWAPP (sequencing with arbitrary primer pairs), in addition to 15 other markers (PCR-RFLP, transposable elements, and resistance to fungicides). The markers revealed a high degree of genetic diversity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
111
0
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 18 publications
16
111
0
10
Order By: Relevance
“…1 and 2). In combination with previous genetic studies, this suggests that B. cinerea is not reproducing in a clonal manner and, instead, is allowing for extensive recombination from either meiotic or mitotic processes to generate a large pool of diversity (Amselem et al 2011;Fournier and Giraud 2008;Fournier et al 2002;Giraud et al 1997Giraud et al , 1999Ma and Michailides 2005;Munoz et al 2002;Rowe and Kliebenstein 2007;Staats and van Kan 2012). This genetic diversity and its phenotypic consequences among the isolates could be what allows B. cinerea to infect such a large number of potential plant hosts.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1 and 2). In combination with previous genetic studies, this suggests that B. cinerea is not reproducing in a clonal manner and, instead, is allowing for extensive recombination from either meiotic or mitotic processes to generate a large pool of diversity (Amselem et al 2011;Fournier and Giraud 2008;Fournier et al 2002;Giraud et al 1997Giraud et al , 1999Ma and Michailides 2005;Munoz et al 2002;Rowe and Kliebenstein 2007;Staats and van Kan 2012). This genetic diversity and its phenotypic consequences among the isolates could be what allows B. cinerea to infect such a large number of potential plant hosts.…”
Section: Discussionmentioning
confidence: 79%
“…B. cinerea is a necrotrophic fungal plant pathogen with an extremely broad host range and is responsible for postharvest crop loss across the globe (Williamson et al 2007). Further, B. cinerea is known to have a large amount of standing genetic variation (Aguileta et al 2012;Alfonso et al 2000;Atwell et al 2015;Baraldi et al 2002;Fournier and Giraud 2008;Fournier et al 2002;Giraud et al 1997Giraud et al , 1999Ma and Michailides 2005;Munoz et al 2002;Rowe and Kliebenstein 2007;Staats and van Kan 2012). Several studies have shown that this genetic diversity within B. cinerea not only contributes to differential virulence in planta (Calpas et al 2006;Denby et al 2004;Rowe and Kliebenstein 2008;Schumacher et al 2012) but can also contribute to the development of fungicide resistant genotypes (Kretschmer et al 2009).…”
mentioning
confidence: 99%
“…Initial molecular investigation of French and Chilean populations of B. cinerea had shown that the species is composed of two sympatric species, transposa and vacuma, characterized by the presence of two transposable elements, Boty and Flipper, or by absence of both of them (Giraud et al, 1997(Giraud et al, , 1999Muñoz et al, 2002). Afterwards, boty (containing only Boty) (Giraud et al, 1999;Muñoz et al, 2002;Vaczy, 2009;Fekete et al, 2012) and flipper (containing only Flipper) (Albertini et al, 2002;Beever & Weeds, 2004;Isenegger et al, 2008;Vaczy, 2009;Fekete et al, 2012) isolates were found, suggesting a more complex population structure of B. cinerea than it was previously recognized. Additional molecular studies of different nuclear genes have shown that B. cinerea population is grouped in two genetic entities -Group I and Group II.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence or absence of the transposons Boty and Flipper in the genome, two sub-populations, transposa and vacuma, have been reported in B. cinerea (Giraud et al, 1997(Giraud et al, , 1999Levis et al, 1997). The transposable elements Boty and Flipper were described for the first time by Diolez et al (1995) and Levis et al (1997), respectively.…”
Section: Survival Inoculum Sources and Dispersalmentioning
confidence: 99%
“…Transposa isolates carry Boty and Flipper, whereas both of these transposable elements are absent in vacuma isolates (Giraud et al, 1997). Isolates carrying either Boty or Flipper in the B. cinerea genome have also been described (De Miccolis Angelini et al, 2003;Giraud et al, 1999;Muñoz, et al, 2002). In addition, the presence of Boty and Flipper has been found in Chilean populations of B. cinerea that affect table grapes, and transposa is the most common isolate (Esterio et al, 2011).…”
Section: Survival Inoculum Sources and Dispersalmentioning
confidence: 99%